PENERAPAN MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA MAS RAUDHATUL ULUM MERANTI - Muhriyeh, Muhriyeh; Mashudi, Mashudi; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis aims to determine the effect of the application of the Discovery learning model on the critical thinking skills of class X students on economic subjects at MAS Raudhatul Ulum Meranti regency district. The research method used is the experimental method with the One-group pre-test post-test design and quantitative research forms. The source of this research data is the students of class X A at MAS Raudhatul Ulum Meranti in Kubu Raya district with a total of 29 students but only 25 students were taken. Data collection techniques used consist of: 1. Data measurement techniques (tests) 2. Observation 3. Documentation. While the data collection tools used are 1. Test questions (essays) 2. Checklist 3. Documents. Data obtained from the answer form questions in the form of descriptions. Data is processed and analyzed with statistics. The technique and data analysis used is to find the difference between the results before and after the Discovery learning model is applied by using the gain score obtained by 0.58 in the medium category. The results of the study prove that there is an increase in critical thinking skills in class X students using the model of Discovery learning in economic subjects at MAS Raudhatul Ulum Meranti in the district of Kubu Raya. Keywords: Discovery Learning Model and Critical Thinking Skills